ANALISIS PARAMETER FISIS SERAPAN DAN DIMENSI CITRA PHANTOM HASIL TOMOGRAFI KOMPUTER MENGGUNAKAN SOFTWARE BRILLIANCE CT DAN IMAGEJ - , EMERITA SETYOWATI, Dr. Gede Bayu Suparta ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Physical parameters analysis of absorption and dimension on Computed Tomography (CT) phantom image produced by 64-multi-slice CT at the Dr. Sardjito General Hospital Yogyakarta has been accomplished. Scanning process based on the same protocol for scanning the patientsâ brain, abdomen and chest. Furthermore, the reconstructed image was analyzed based on material absorption, diameter dimensions, and seven rows acrylic pin hole dimension readings of multi-pin layer using computed tomography software in Digital Imaging Communications in Medicine (DICOM) image format and ImageJ software in DICOM and Joint Photographic Experts Group (JPEG) image format. The readings on material absorption measurements using Brilliance CT software in Hounsfield Units (HU) was linear in accordance to the reference value, as well as the measurement using ImageJ software on DICOM image format. On measurement results using ImageJ, the JPEG format was not linear due to the effect of compression of 16 bits to 8 bits images. Diameter dimensions measurements using Brilliance CT software in DICOM format and ImageJ both DICOM and JPEG format image reconstruction results were linear with respect to the actual dimensions. In the seven row acrylic pin holes in multi-pin layer measurement using Brilliance CT software was linear with respect to the actual dimensions. The smallest dimension that can be measured was 2 mm. Measurements using ImageJ software for DICOM and JPEG format was linear with respect to the actual dimensions. The smallest dimension that can be measured using ImageJ software was 1 mm.